ANALISIS PERUBAHAN UPACARA ADAT BATAK TOBA DALAM UPACARA SUASANA SUKACITA DI KELURAHAN KULIM KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Panggabean, Mosar Anggiat; Hambali, Hambali; Eddison, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study is to analyze the Batak customary ceremony in the festive atmosphere of Pekanbaru City, Tenayan Raya District, Kulim Village and To find out what is the reason for the change in Batak customary ceremony in Pekanbaru City, Tenayan Raya District, Kulim District ". The population in this study was all heads and housewives of Toba Batak ethnic Christians or Catholics in Tenayan Raya district, Kulim District, with a population of 27,764 residents. The sample of this study was 30 people, 3 of whom were Batak Indigenous leaders, while 27 were Other people are Batak Toba people: This technique of data collection is observation, questionnaire, interview, and documentation. happy in Pekanbaru City, Tenayan Raya District, Kulim Village overall, of the 30 respondents who said Yes (48%) while those who answered No (52%) meant that there was a change or a shift in the form of traditional Batak Toba ceremony in a festive mood in Pekanbaru City, Tenayan Raya District, Kulim Village. Although the ceremonies were joyful in the city of Pekanbaru, Tenayan Raya district, Kulim Village overall, out of the 30 respondents, many said Yes (43%) while those who answered No (57%) meant that there was a change or shift in procedure for Batak Toba customary ceremony. in the festive mood of the Pekanbaru City Tenayan Raya District Kulim Village. The change in the form and procedure of the Batak Toba ritual in the atmosphere of happiness was due to several factors influencing all respondents who answered Yes (52%) and those who answered No (48%). These factors include the impact of increases and declines, formal and advanced education, and natural factors.Key Words : Change, Joy Ceremony, Toba Batak Traditional